Different Doses of Pharmacological Treatments for Mild to Moderate Alzheimer’s Disease: A Bayesian Network Meta-Analysis - Zhang, Tingting; Liu, Nanyang; Cao, Hongfu; Wei, Wei; Ma, Lina; Li, Hao (Frontiers in Pharmacology, 2020)
Background: Pharmacological treatments play a significant role in treating mild to moderate Alzheimer’s disease (AD), but the optimal doses of various drugs used for these treatments are unknown. Our study compared the efficacy, acceptability, and safety of different doses of pharmacological treatments for mild to moderate AD. Methods: Randomized controlled trials (RCTs) were identified by searching the PubMed, EMBASE, and Cochrane Library databases (all RCTs published from the date of inception of the databases until September 19, 2019). Trials comparing the efficacy, acceptability, and safety of pharmacological interventions involving donepezil, galantamine, rivastigmine, memantine, huperzine A, and Ginkgo biloba extract EGb761, alone or in combination, were identified. The primary outcomes were efficacy, acceptability, and safety. Results: Our meta-analysis included 37 studies involving 14,705 participants. In terms of improving cognitive function, galantamine 32 mg, galantamine 24 mg, donepezil 5 mg, and donepezil 10 mg were more effective than other interventions, with the surface under the cumulative ranking curve (SUCRA) values of 93.2%, 75.5%, 73.3%, and 65.6%, respectively. According to the SUCRA values, EGb761 240 mg was considered to be the optimal intervention in terms of both acceptability and safety. With regard to clinical global impression, rivastigmine 12 mg had the highest probability of being ranked first (83.7%). The rivastigmine 15 cm2 patch (SUCRA=93.7%) may be the best choice for daily living. However, there were no interventions that could significantly improve neuropsychiatric symptoms, compared with the placebo. Conclusions: Different doses of the tested pharmacological interventions yielded benefits with regard to cognition, acceptability, safety, function, and clinical global impressions, but not effective behaviors.